Understanding performance management in primary care. Issue 1 (13th February 2017) - Rogan, Lisa; Boaden, Ruth
Abstract : Purpose: Principal-agent theory (PAT) has been used to understand relationships among different professional groups and explain performance management between organisations, but is rarely used for research within primary care. The purpose of this paper is to explore whether PAT can be used to attain a better understanding of performance management in primary care. Design/methodology/approach: Purposive sampling was used to identify a range of general practices in the North-west of England. Interviews were carried out with directors, managers and clinicians in commissioning and regional performance management organisations and within general practices, and the data analysed using matrix analysis techniques to produce a case study of performance management. Findings: There are various elements of the principal-agent framework that can be applied in primary care. Goal alignment is relevant, but can only be achieved through clear, strategic direction and consistent interpretation of objectives at all levels. There is confusion between performance measurement and performance management and a tendency to focus on things that are easy to measure whilst omitting aspects of care that are more difficult to capture. Appropriate use of incentives, good communication, clinical engagement, ownership and trust affect the degree to which information asymmetry is overcome and goal alignment achieved. Achieving the right balance between accountability and clinical autonomy is important to ensure governance and financial balance without stifling innovation. Originality/value: The principal-agent theoretical framework can be used to attain a better understanding of performance management in primary care; although it is likely that only partial goal alignment will be achieved, dependent on the extent and level of alignment of a range of factors.